Chemical, Microbiological, and Functional Characterization of Kefir Produced from Cow’s Milk and Soy Milk - Raúl Ricardo Gamba; Shihori Yamamoto; Mahmoud Abdel-Hamid; Tetsuya Sasaki; Toshihide Michihata; Takashi Koyanagi; Toshiki Enomoto (International Journal of Microbiology)
Kefir is a functional beverage that contains lactic and acetic acid bacteria (LAB, AAB) and yeasts. This work’s aim was to study the chemical, microbial, and functional characteristics of kefir produced from cow’s milk and soy milk. After fermentation, free amino acids were 20.92 mg 100 mL−1 and 36.20 mg 100 mL−1 for cow’s milk and soy milk kefir, respectively. Glutamic acid was majority in both, suggesting that microbial proteolysis leads to an increase in free amino acids including glutamic acid. 108–109 CFU mL−1 LAB, 106–107 CFU mL−1 AAB, and 106–107 CFU mL−1 yeasts were counted in cow’s milk kefir, whereas soy milk kefir contained greatly lower yeasts and AAB. Lactococcus lactis, Kazachstania unispora, and Saccharomyces cerevisiae were isolated as major microorganisms in both kefirs. Acetobacter orientalis only existed in cow’s milk kefir. Cow’s milk and soy milk showed ACE inhibitory activity, which significantly increased after fermentation. Both kefirs also exhibited antioxidant activity and bactericidal activity against Escherichia coli, Salmonella Typhimurium, and Staphylococcus aureus.